Deradikalisasi Agama Melalui Integrasi Nilai Moderasi Beragama dalam Pembelajaran PAI di SMAN 1 Pamekasan - Fithriyah, Sayyi Sayyi (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2023)
The presence of the era of society 5.0 is a challenge for the creation of an inclusive nation, tolerant and harmonious nation in the midst of the rapid flow of information that can be accessed and accepted by the wider community without borders, the condition of the nation which in percentage terms is 55% is not ready for the birth of this era, as a result it creates a nation that tends to being extremist, radical and intolerant of the information he received could not be properly filtered and clarified. The purpose of this research is to explore the value of religious moderation and reveal the strategy of integrating these values in PAI (Islamic Religious Education) at SMAN 1 Pamekasan which has made efforts to deradicalize the religion of its students. This study used a qualitative approach with case study design. Research data was obtained through observation, interviews, and document studies related to deradicalization of religion through the integration of various moderation values in PAI (Islamic Religious Education). The results showed that the religious moderation values include values of tolerance, egalitarianism, balance, harmony, inclusiveness, humanism, equality, love of the motherland, mutual respect, forgiveness, mutual help, fairness, consistency, discipline, and independence values. These values are integrated in PAI (Islamic Religious Education) through various integration approaches and strategies, namely; traditional integration strategy, free integration strategy, reflective integration strategy, transdisciplinary integration strategy, and trans-internal integration strategy.